Effects of ionization on stability of 1-methylcytosine — DFT and PCM studies - Raczyńska, Ewa D. (J Mol Model, 2016)
Consequences of ionization were studied by quantum-chemical methods (DFT and PCM) for 1-methylcytosine (MC)—a model of the nucleobase cytosine (C) connected with sugar in DNA. For calculations, three prototropic tautomers (one amino and two imino forms) and two imino zwitterions were considered, including conformational or configurational isomerism of exo heterogroups. Ionization and interactions between neighboring groups affect intramolecular proton-transfers, geometric and thermodynamic parameters, and electron delocalization for individual isomers. We discovered that an imino isomer is present in the isomeric mixture in the highest amount for positively ionized MC. Its contribution in neutral and negatively ionized MC is considerably smaller. Acid-base parameters for selected radical ions were estimated in the gas phase and compared to those of neutral MC. Gas-phase acidity of radical cations is close to that of the conjugate acid of MC, and gas-phase basicity of radical anions is close to that of the conjugate base of MC. Various routes of amino-imino conversion between neutral and ionized isomers were considered. Energetic-barrier for intramolecular proton-transfer in MC is close to that in the parent system—formamidine. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00894-016-3020-2) contains supplementary material, which is available to authorized users.